IDENTIFIKASI KEMAMPUAN BERPIKIR KREATIF MATEMATIKA POKOK BAHASAN PELUANG - Faelasofi, Rahma (JURNAL e-DuMath, 2017)
AbstractThe purpose of this study is that researchers want to better identify students mathematical creative thinking abilities in solving mathematical problems on the subject of opportunity. This research is a descriptive research conducted at STKIP Muhammadiyah Pringsewu Lampung, with data analysis used is descriptive analysis of quantitative and qualitative. The subjects of this study are students who take basic statistics courses in the academic year 2016-2017. The result of the analysis of the ability of mathematical creative thinking in this study obtained the average value of the smoothness of the aspect reached 65.24; The average aspect of flexibility score reached 45.83; and the average aspect elaboration value reached 66.67. Thus the level of students mathematical creative ability in the subject of opportunity is still low because the new score is 59.26.Keywords : mathematical creative thinking skills, problem solving